El viajero, la fiebre héctica y las horas. Estudio introductorio de un consilium médico de Mateo Boldieri (s. XV) - Alonso Guardo, Alberto (2022)
This paper studies a consilium on hectic fever written by Matthew Boldieri, professor of medicine at the University of Padua, originally from Verona, in the fifteenth century. The work explains the treatment that a patient predisposed to this disease should follow during the course of a journey. We analyse the structure and content of the work, investigate the characteristics of the clinical case in the light of the data extracted from the consilium and, finally, examine the schedule used in the regime that the recipient should follow.
Se estudia un consilium médico sobre la fiebre héctica escrito por el veronés Mateo Boldieri, profesor de medicina en la Universidad de Padua durante el siglo XV. La obra expone el tratamiento que un paciente predispuesto a dicha enfermedad debe seguir durante la realización de un viaje. Analizamos la estructura y contenido de la obra, investigamos las características del caso clínico a la luz de los datos extraídos de la misma y, por último, examinamos el sistema horario empleado en el régimen que debe seguir el destinatario.
Keywords: Medicina medieval; Viajes